(untitled) (Fiep Bulletin - online, 2013)
Introduction: As the muscle tissue component that influences the flexibility, it is important that the musculature is not compromised. One way that this is possible muscle stretching, which can be achieved by techniques such as passive stretching technique and energy muscle. Objective: To compare the immediate and late effects of passive stretching and energy muscle technique on flexibility in healthy women, comparing both techniques. Methods: We evaluated 24 women, age 20 to 30 years, divided into: passive stretching group (GAP) and energy muscle group (GME). We performed a preliminary assessment of range of motion (ROM) for the dominant goniometry member, and soon after the technique was applied to the corresponding group. The measurement of ROM was made shortly after the application of the technique and after 24 hours. Statistical analysis was used with mixed design ANOVA with Bonferroni post-test with an alpha of 0.05. Results: The Bonferroni test showed that the differences in ROM were significant (p < 0,05) at all times of collection. In GME, the Bonferroni test showed significant differences when compared with the pre-intervention (PRE) and immediately after (POST), and p <0,001. Comparing the measures POST and 24 hours after the intervention, it was noticed a small decrease in ROM with respect to POST, p = 0,001. Conclusion: The immediate effect of stretching was increased flexibility that has not remained after 24 hours. The largest increase occurred in the ROM was in the GME, suggesting a greater effectiveness of this technique.